Neospora caninum-induced NETosis in canine colostral polymorphonuclear neutrophils. (December 2022) - Demattio, Lukas; Conejeros, Ivan; Grob, Daniela; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos; Wehrend, Axel
Abstract: Neospora caninum represents an obligate intracellular apicomplexan parasite of the family Sarcocystidae causing severe reproductive disorders in cattle, small ruminants, wild animals and canids worldwide. Neutrophil extracellular traps (NETs) were recently described as effective host defense mechanism of polymorphonuclear neutrophils (PMN) derived from cattle, dogs, goats and dolphins against N. caninum tachyzoites. Nonetheless, nothing is known so far on canine colostral PMN immune reactions against N. caninum although breeding bitches represent a susceptible dog cohort and infected bitches may spread tachyzoites through transplacental transmission to their offspring. Thus, isolated colostrum PMN from bitches were assessed for PMN phagocytic activities as well as NETs release against viable N. caninum tachyzoites. In vitro interactions of canine colostrum-derived PMN with tachyzoites were analyzed at different ratios and time spans. Extracellular chromatin staining was applied in order to unveil classical molecules of NETs, such as neutrophil elastase (NE), global histones (H1, H2A/H2B, H3, H4) and myeloperoxidase (MPO), via antibody-based immunofluorescence microscopy analysis. N. caninum tachyzoites induced canine NETs in colostral PMN and scanning electron microscopy (SEM) analysis revealed NETs formation by colostral PMN thereby ensnaring tachyzoites after exposure. In summary, NETs released from canine colostral PMN might represent an early and effective maternal defense mechanism of the definitive host helping neonates to reduce initial intracellular replication of not only parasites but of other invasive pathogens after colostrum consumption. Highlights: Neutrophil extracellular traps (NETs) were described as effective host defense mechanism of polymorphonuclear neutrophils (PMN) against N. caninum tachyzoites. Nonetheless, nothing is known so far on canine colostral PMN immune reactions against N. caninum. Thus, isolated colostrum PMN from bitches were assessed for PMN phagocytic activities as well as NETs release against viable N. caninum tachyzoites. NETs released from canine colostral PMN might represent an early and effective maternal defense mechanism helping neonates to reduce initial intracellular replication of not only parasites but of other pathogens after colostrum consumption.